Transcriptional regulation of antimicrobial peptides in mucosal tissues of Atlantic cod Gadus morhua L. in response to different stimuli. Issue 12 (8th February 2013) - Ruangsri, Jareeporn; Lokesh, Jep; Fernandes, Jorge M.O.; Kiron, Viswanath
Abstract To understand the physiological roles of antimicrobial peptide (AMP) families in Atlantic cod, fish were subjected to abiotic (crowding/temperature rise) or biotic (commensal or pathogenic bacterium) stimuli, following which the transcriptional profiles of piscidin 1 (pis1), piscidin 2 (pis2), beta defensin (defb), hepcidin (hep) and cathelicidin 1 (cath1) in selected mucosal tissues were analysed using qPCR. Unlike the crowding condition, the temperature change affected the transcripts of AMP genes – after the rise in temperature (0 h), cath1 was downregulated mainly in gills, defb was downregulated in gills and skin, while hep was downregulated in gills, skin and rectum. These gene transcripts returned to their basal levels at 72 h, by which time pis1 gene was upregulated in gills and skin. The pis2 gene was apparently not altered by temperature change. Bath exposure to commensal bacterium affected only defb gene in gills (downregulated) and skin (upregulated). Bath challenge with live pathogen upregulated cath1 gene mainly in gills, and hep gene in gills, skin and rectum, while pis1 and pis2 genes remained unaltered. The differential modulation of the AMP genes examined suggests that these peptides maintain distinct functions with respect to mucosal defence mechanisms in Atlantic cod.